Selective removal of heavy metal ions in aqueous solutions by sulfide-selector intercalated layered double hydroxide adsorbent. Issue 9 (September 2019) - Wang, Jing; Zhang, Liang; Zhang, Tianshu; Du, Ting; Li, Tao; Yue, Tianli; Li, Zhonghong; Wang, Jianlong
Abstract: Remaining largely under-appreciated, a majority of metal ion sorbents are limited in their target selectivity. In this work, a 3D sulfide intercalated NiFe-layered double hydroxide (NFL-S) hierarchical sorbent has been synthesized for selective heavy metal removal. The intercalation of sulfurated groups in the interlayer of the layered double hydroxide (LDH) nanosheets endows NFL-S as a selective heavy metal ion filter; the selectivity of NFL-S for heavy metals is in the order of Pb 2+ > Cu 2+ ≥ Zn 2+ > Cd 2+ > Mn 2+, and NFL-S has high kd values for Pb 2+ (∼10 6 mL/g) and Cu 2+ (∼10 5 mL/g). Scanning electron microscopy, X-ray photoelectron spectroscopy and powder X-ray diffraction were used to analyze the composition of the as-prepared nanoadsorbent. The selective adsorption behavior was systematically studied using batch experiments, and the performance was evaluated through kinetic and isotherm studies. Moreover, the adsorption mechanism of heavy metals by NFL-S through surface complexation was also investigated, which shows great potential for water decontamination.